Determination of Teachers' Awareness of Environmental Ethics - Kılınç, Alparslan; Kızmaz, Sevim; Taşkıran, Şeyma Aksakal; Emre, İrfan (Durmuş BURAK, 2024)
Environmental ethics defines the moral principles governing the relationship between humans and their environment, emphasizing the need for harmony with nature. Raising awareness about environmental issues is believed to be achievable through education, with teachers playing a critical role in this process. This study aims to assess the level of environmental ethics awareness among teachers from various disciplines(classroom,science and social studies teachers) and examine whether variables such as gender, age, field, seniority, educational background, and academic status influence their opinions. The research employed a quantitative survey method, involving 346 teachers from public schools in Elazığ. Participants completed a personal data form and the Environmental Ethics Awareness Scale. The data were analyzed using the MANOVA test. Results indicated no significant differences across all sub-dimensions for teachers graduating from faculties outside the Faculty of Education. However, a significant difference was observed regarding the field variable, while other variables like gender, age, and seniority showed no significant differences. Arithmetic means of teachers’ responses revealed that most opinions were at the "Agree" level across the sub-dimensions, except for specific items. These findings suggest that while teachers generally exhibit awareness of environmental ethics, their views vary depending on their field of expertise. This study highlights the importance of integrating environmental ethics into educational practices to further enhance teachers’ awareness and their ability to address environmental issues effectively. Future research could expand on these findings by exploring other variables and methodologies to provide deeper insights into teachers' environmental ethics awareness.
Keywords: Teacher Education and Professional Development of Educators; Öğretmen Eğitimi ve Eğitimcilerin Mesleki Gelişimi